Karakteristik Jaringan Ulama Nusantara menurut Pemikiran Azyumardi Azra - Nurdinah Muhammad (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Study on transmission and spread of purifying ideas in 17th and 18th centuries focuses on the role of ulama, that Azyurmadi specifically stress on the   importance of Tasawuf and rationality. He opines the tasawuf is  one of the other  side of Islam. Shariah and Fiqh are on one side, while the second side is tasawuf. Islamization would be perfect if both sides are combined together; the fiqh and the  tasawuf. If mankind only stresses on one of them, let‟s say fiqh only, the plurality  of human life will be brought to the legalistic tendencies. Therefor. the mystical   understanding on religious teaching is required. That is why Azyumardi highly  appreciates zikir and alike that make mankind become closer to Allah.